A coupled–channels model describing the low-lying 2Δ, 2Σ+ and 2Π electronic states of nickel monohydride with experimental accuracy. (September 2021) - Havalyova, I.; Bozhinova, I.; Pashov, A.; Ross, A.J.; Crozet, P.
Highlights: NiH high resolution spectroscopy. Ground state supermultiplet. Fully Quantum mechanical coupled-channels depertrubation. Abstract: A detailed study of the three interacting low-lying electronic states 2 Δ, 2 Σ + and 2 Π of NiH –the so called "supermultiplet" – is presented. A coupled-channels model reproduces the experimental term values of 58 NiH, 60 NiH and 62 NiH with accuracy very close to the estimated uncertainty of 0.01 cm − 1 . The model is based on a set of Hund's case (a) potential curves and R -dependent coupling functions. In addition to the expected spin-orbit and various rotational couplings between the zero-order states, second-order effects are found to be important. The spin-orbit interaction is large compared to the separations between these electronic states, so that most of the observed rovibrational levels are strong mixtures of the Ω components of the multiplet. The fitting procedure proved difficult because there were no perturbation-free data to determine the starting values for the model functions. For the potential curves we were guided by previous effective Hamiltonian models; ab initio predictions supplied starting values for the spin-orbit and the rotational coupling functions. We believe that this model may be reliably extrapolated to higher rotational levels, with potential applications in the simulation of high temperature spectra, for example in the context of stellar atmospheres.